Cutaneous leiomyomas mimicking keloids - Dimitrov, Dimitre; Reszke, Radomir; Hamodat, Mowafak Mohamed; Szepietowski, Jacek (Dermatology Review/Przegląd Dermatologiczny, 2016)
Introduction . Cutaneous leiomyomas are rare, benign smooth muscle neoplasms of the skin. According to the origin of the tumor, there are three types of cutaneous leiomyomas: piloleiomyomas, angioleiomyomas and genital leiomyomas. Objective . To present an uncommon case of cutaneous leiomyomas which, due to clinical similarities, had been previously misdiagnosed and managed as keloids. Case report. A 23-year-old woman with Fitzpatrick skin type 4/5 was referred to the outpatient department of dermatology for treatment of keloids on the left shoulder. After examination we decided to take a skin biopsy for histopathological and immunohistochemical investigation, which revealed cutaneous leiomyomas. Conclusions . Cutaneous leiomyomas may be misdiagnosed as keloids. The former are of clinical relevance as they may denote hereditary leiomyomatosis and renal cell cancer. Early recognition is of paramount importance and may be life-saving.